Tooth size discrepancies in Kosovar adolescents with different malocclusion classes - Zylfiu-Latifi, Blertë; Kamberi, Blerim; Meštrović, Senka (Anthropological Review, 2023)
The goal of this study was to evaluate tooth size discrepancies in Kosovar adolescents according to the Bolton’s analysis, and to determine the differences between gender and malocclusion classes. A sample of 400 Kosovar adolescents, aged 13–19 years with various malocclusion categories (class I, II, III) according to the Angle’s classification, was randomly selected. The anterior tooth size ratio, overall tooth size ratio, posterior tooth size ratio, as well as distribution of tooth size discrepancies were assessed. The normality of distribution was assessed by the Kolmogorov-Smirnov test, the differences between genders by the Independent Sample T-test, the Mann-Whitney U-test, and differences among malocclusion groups by ANOVA, the Kruskal-Wallis, and the Dunn’s post-hoc tests. The tooth size ratios of men and women did not differ significantly. The results also demonstrated significant differences among the malocclusion classes only for the anterior tooth size ratio (p<0.05). The overall and posterior ratios did not differ significantly within malocclusion classes. The percentages of Kosovar subjects with a deviation of more than 2SD from the Bolton average for the anterior and overall ratios were 41.37 and 23.79, respectively. The genders did not differ significantly regarding tooth size ratios. Among the malocclusion classes, the anterior ratio differed significantly. In Kosovar subjects, tooth size discrepancies tend to be higher compared to Bolton’s averages.